(untitled) (Journal of Computational Mathematics, 2018)
In this paper, we propose an algorithm for isolating real roots of a given univariate spline function, which is based on the use of Descartes' rule of signs and de Casteljau algorithm. Numerical examples illustrate the flexibility and effectiveness of the algorithm.